Penguatan Kualitas Visual untuk Meningkatkan Engagement Media Sosial: Pratik Produksi Fotografi di Harian Disway - Calista Salsabila Azhari; Doan Widhiandono (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Photography in digital content is one of the key strategies for increasing audience engagement, particularly through social media platforms. As a digital daily media outlet, Harian Disway utilizes photography to maintain reader interest while expanding the reach of its content. This study aims to analyze the role of photography in enhancing engagement on Harian Disway content and to identify the types of photographic content that are most effective in capturing audience attention in the digital era. This research employs a case study method with a qualitative approach through content analysis of Harian Disway social media platforms. The findings indicate that photographic content featuring elements of human interest, timeliness (actuality), and high visual quality tends to generate higher levels of interaction compared to text-based content. These results demonstrate that photography plays a strategic role in supporting the effectiveness of digital media communication and contributes to the development of visual journalism studies and media content management.